The Ambivalence In Hisaye Yamamoto’s Seventeen Syllables - Trisnawati, Ai; Wiranti, Ida; Faujiah, Neuis Nurul; Amindari, Seftiani; Wartini, Titin (Peneliti.net, 2024)
This study aims to reveal the ambivalence in the short story Seventeen Syllables (1988) by Hisaye Yamamoto. This study uses qualitative methods.